Jovens e os Stories do Instagram: estudo netnográfico durante a pandemia da Covid-19 - Angeluci, Alan César Belo; Passarelli, Brasilina; Falandes, Carolina Gois [UNESP]; Garcia, Milena Possar (University of Borås, 2023)
Introduction. This study examined the media and information literacies of young Brazilians on their main profiles and Dix on Instagram during the Covid-19 pandemic. Method. A netnography (a variation of online ethnography) was conducted in three stages: participant observation, web scraping, and video interviews with young people aged 15 to 18 in the metropolitan region of São Paulo, following Bardin's Content Analysis. Analysis. Of the profiles analysed, 89.7% of the main ones were open, while all the Dix were closed. The use of hashtags in Dix occurred in only 8.3%, and the majority of profiles used the carousel feature, with 72.4% on the main profiles and 58.3% on Dix. The use of nicknames was less common on the main profiles (24.1%) compared to the majority of Dix (83.3%). Results. Young people strategically posted content on their main profiles, improving image quality with features and filters. In Dix, everyday posts, humour, and sensitive topics prevailed, with less image editing, anticipating the photo dump phenomenon. Conclusion. By managing these spaces, young people can assume different identities, with media and information literacies being important resources for their online practices and expression of feelings.
Keywords: Covid-19; Information literacy; social media